Rudolph Forster papers - Forster, Rudolph, 1872-1943.
Correspondence, memoranda, notes, invitations, clippings, telegrams, and other papers accumulated by Forster while executive clerk and secretary to U.S. presidents from 1897 to 1943. The material predominantly relates to the Theodore Roosevelt, Woodrow Wilson, and Franklin D. Roosevelt administrations. Includes handwritten notes and memoranda from most of the presidents, several drafts and signed printed copies of presidential proclamations, and social notes.
Library of Congress Prints and Photographs Division.
Secretary to U.S. presidents William McKinley through Franklin D. Roosevelt.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Selection of Forster's papers from the administration of President Woodrow Wilson was given to the Library in 1941 and was transferred to the Rudolph Forster papers in 1979.
Keywords: McKinley, William, -- 1843-1901.; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919.; Wilson, Woodrow, -- 1856-1924.; Presidents -- United States -- Staff; United States -- Politics and government -- 20th century; Secretaries, Presidential